PENGENDALIAN SOSIAL OLEH GURU PADA SISWA YANG BERPERILAKU AGRESI DI SMP HARUNIYAH PONTIANAK TIMUR - Rizwan, Rizwan; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "Social Control by Teachers on Students Who Aggression in Haruniya junior high school East Pontianakâ€. The problem in this study is how social control by teachers on student who aggression in Haruniya junior high school East Pontianak with sub-problem is how social control by teachers to students who aggression through socialization and punishment at Haruniya Junior High School. This study uses descriptive qualitative methods. The data collection tool uses observation guidelines, interview guidelines and documentation studies. The results of the study show (1) preventive social control by the teacher on students who behave aggressively through socialization actions have been carried out by the teacher well, it is evident that the teacher always provides motivation, advice, patience, discipline, and reminds about school discipline (2) refresive social control by teachers to students who behave aggressively through punitive actions still not good because some teachers still apply negative penalties such as physical punishment, scolding and yelling at students. But, some teachers apply positive penalties such as doing assignments, writing, compliments and calling parents.Keywords: Social Control, Aggression Behavior, Socialization and Punishment